Effects of light quality on growth and development of cucumber seedlings in controlled environment - Jinxiu, Song; Qingwu, Meng; Weifen, Du; Dongxian, He (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Conventional light sources have been successfully used to cultivate a wide variety of horticultural crops. However, they are of limited use due to uncontrollability of spectra and energy inefficiency. Light-emitting diodes (LEDs) emerged with tremendous potential in controlled environment agriculture due to their energy efficiency, longevity, and spectral specificity, but the effects of different types of LEDs on plant growth and development must be examined. In this study, cucumber (Cucumis sativus L. cv. Zhongnong 26) seedlings were grown under four different lighting treatments that each delivered a photosynthetic photon flux density of 200 µmol/m2•s at plant canopy including triphosphate fluorescent lamps (TF), high-frequency fluorescent lamps (HF), white LEDs (WL), and red and blue LEDs (RBL). Cucumber seedlings were grown in a growth chamber at (25.0±1.5)°C with 12-hour light and 12-hour dark for 30 days after sowing, and data were subsequently collected. Seedlings grown under the WL were 45%, 12%, and 40% taller than those grown under the TF, HF and RBL, respectively. The leaf area was 23% smaller under the TF than under the HF. The shoot dry weight was 16%-22% lower under the TF than under the other lighting treatments. The transplants grown under the RBL had the lowest root dry weight and root to shoot ratio. The seedling quality index was similar among all the lighting treatments. The LEDs treatment yielded more total dry weight with unit electric power compared to the fluorescent lamps. The chlorophyll content was 13%-15% higher in plants grown under the HF and WL than that under the TF and RBL. Plants grown under the WL and RBL had greater photosynthetic rate, transpiration rate, and stomatal conductance than those grown under the TF and HF. It was concluded that high quality cucumber seedlings can be efficiently produced under the broad-spectrum WL that emit a reasonable amount of blue, green and red light, and the lack of green light and/or high ratio of red to blue light under the RBL may cause undesired plant attributes.Keywords: blue light, chlorophyll, cucumber seedlings, controlled environment, gas exchange, green light, light-emitting diode, red lightDOI: 10.3965/j.ijabe.20171003.2299Citation: Song J X, Meng Q W, Du W F, He D X. Effects of light quality on growth and development of cucumber seedlings in controlled environment. Int J Agric & Biol Eng, 2017; 10(3): 312–318.